Acute ophthalmoparesis in the anti-GQ1b antibody syndrome: electrophysiological evidence of neuromuscular transmission defect in the orbicularis oculi. Issue 3 (13th February 2004) - Lo, Y L; Chan, L L; Pan, A; Ratnagopal, P
Abstract : Objective: To prospectively study anti-GQ1b antibody positive cases of acute ophthalmoparesis (AO) clinically and electrophysiologically. Methods: Nine consecutive cases presenting with predominantly acute ophthalmoplegia were assessed clinically and had stimulated single fibre electromyography (SFEMG) of the orbicularis oculi at presentation. All had magnetic resonance imaging brain scans and anti-GQ1b antibody titres determined. Results: Four cases had elevated anti-GQ1b antibody titres and abnormal SFEMG studies, which improved in tandem with clinical recovery over three months. Five other anti-GQ1b antibody negative cases were diagnosed as diabetic related cranial neuropathy, idiopathic cranial neuropathy, ocular myasthenia gravis, and Tolosa-Hunt syndrome. All five cases showed complete recovery over a three month period. Conclusions: This study demonstrated electrophysiologically the dynamic improvement of neuromuscular transmission of anti-GQ1b antibody positive cases of AO, in tandem with clinical recovery. SFEMG is of value in differentiating weakness due to neuromuscular transmission defect from neuropathy in these clinical situations.